Layered heterogeneous light-weight high-manganese steel containing nano precipitates and preparation method of layered heterogeneous light-weight high-manganese steel
By using layered isomerized high-manganese steel containing nanoprecipitates in liquid hydrogen storage tank steel, the problems of high cost of existing materials and poor resistance to delayed fracture are solved, and the effects of high strength, excellent elongation and good anti-hydrogen embrittlement are achieved.
Patent Information
- Application Number
- CN202411641083.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-28
AI Technical Summary
The existing liquid hydrogen storage tank steel has high cost, low temperature strength and toughness mismatch, and poor resistance to delayed fracture.
Laminated isomerized lightweight high manganese steel containing nanoprecipitates is used to regulate the size and distribution of nanoprecipitates through warm rolling to form microstructures of austenite, martensite and nanoprecipitates, and combine specific chemical compositions and process treatments to improve the strength and elongation of the material.
While ensuring yield strength and tensile strength, the elongation and hydrogen embrittlement resistance of the material are significantly improved, making it suitable for liquid hydrogen storage tank applications.
Smart Images

Figure BDA0005138463810000061 
Figure BDA0005138463810000071 
Figure BDA0005138463810000072
Abstract
Description
Technical Field
[0001] The invention relates to a liquid hydrogen storage tank steel and a preparation method thereof, in particular to a layered heterogeneous light high manganese steel containing nano-precipitates and a preparation method thereof. Background Art
[0002] At present, the mature steel materials for liquid hydrogen storage tanks on the market are 304L, 316 and austenitic stainless steel containing 9% Ni. These steels are not only expensive, but also have problems such as mismatched low-temperature strength and toughness and poor resistance to hydrogen-induced delayed fracture. In order to solve the existing problems in this technical field, in recent years, Chinese and foreign countries have successively developed low-temperature high-manganese steels and successfully put them into use in the field of liquefied natural gas storage and transportation. They all adopt the "Mn instead of Ni" alloy composition design to greatly reduce costs. This is because the Mn element can also improve the low-temperature stability of austenite, and high-manganese austenitic steel does not exhibit ferromagnetism at low temperatures.
[0003] Layered heterogeneous structures in metals are considered to have great research potential and are now a hot research direction, especially how structural parameters such as the interlaminar spacing, lamina size, and the ratio of different lamina in the layered heterogeneous organization affect the strength and plasticity of metal materials. The preparation of layered heterogeneous single metal / composite metal materials with excellent strength-plasticity matching and the revelation of the intrinsic relationship between their structure and mechanical properties are of great significance to the continuous development of the traditional metallurgical industry and metal materials.
[0004] After searching:
[0005] The document with Chinese patent publication number CN106191404B discloses "A method for preparing high-strength and high-plasticity TWIP steel", which is a method of obtaining ultra-fine grains below 1μm by asynchronous rolling with ultra-large deformation and cold rolling combined with annealing treatment. At the same time, with the addition of microalloys such as Nb and Ti, it can achieve a tensile strength of 1400MPa and an elongation of more than 7%. The invention requires warm rolling at 400℃ followed by cold rolling, a total deformation of more than 95%, and asynchronous rolling. The process is complex and difficult, and it is not feasible for large-scale industrial production.
[0006] The document with European patent document number EP3492618B1 discloses "A 1500MPa grade high strength and plasticity product steel for automobiles", whose chemical elements are as follows: C 0.1%, 0.3%, Si 0.1%~2.0%, Mn 7.5%~12%, A10.01%~2.0% by mass; the balance is iron and other inevitable impurities; the microstructure of the invented steel is austenite + martensite + ferrite or austenite + martensite, which can reach 1500MPa level, and its strength and plasticity product is not less than 30GPa%. However, the austenite in the invented microstructure is a metastable structure, and martensitic transformation will occur during the deformation process, so the low temperature toughness and shear edge properties will be adversely affected. Moreover, the invented steel requires very complex and time-consuming multi-step heat treatment, and its production efficiency and cost are very unfavorable.
[0007] Adding a certain amount of Al to the existing low-temperature high-manganese steel is considered to be one of the most promising strategies to significantly improve the hydrogen embrittlement resistance. It can not only form an Al2O3 film layer on the surface of the matrix to greatly reduce the diffusion rate of hydrogen atoms, but also inhibit the martensitic phase transformation to reduce the sensitivity to hydrogen embrittlement. In addition, Al easily combines with Fe and Mn elements in steel to form κ-carbides, which precipitate within the crystal or along the intergranular, while affecting the material's strength and toughness performance and hydrogen embrittlement resistance. When κ-carbides are dispersed and precipitated in nanometer size within the crystal, they can act as traps to absorb some hydrogen atoms, increase the critical concentration of hydrogen embrittlement and hydrogen embrittlement resistance; on the contrary, when κ-carbides are densely precipitated in a network form along the grain boundary, microcracks will form to cause quasi-dissociation fracture, which will damage the macroscopic fracture performance. Therefore, controlling the precipitation behavior and state of κ-carbides and related metastable phases is very critical to the material's hydrogen embrittlement resistance. Summary of the invention
[0008] The object of the present invention is to provide a layered heterogeneous lightweight high manganese steel containing nano-precipitates, and a preparation method thereof, wherein nano-precipitates in the lightweight high manganese steel are regulated by warm rolling, and the yield strength is ensured to be 900-1200 MPa, the tensile strength is 1100-1320 MPa, the microstructure is austenite, martensite and nano-precipitates, the precipitates with a size of 2-50 nm account for a volume ratio of not less than 1.6%, and the elongation is ≥20%.
[0009] Measures to achieve the above objectives:
[0010] A layered heterogeneous light high-manganese steel containing nano-precipitates, the components and weight percentage contents of which are: C≤0.5%, Si≤0.5%, Mn: 20.0-26.0%, Al: 5-12%, Cr≤7%, Cu: 0.5-5.0%, Ni: 0.5-1.5%, Nb: 0.01-0.5%, S≤0.006%, P≤0.015%, N≤0.001%, and the remainder is Fe and unavoidable impurities; and the addition amount of Al is one quarter to one half of the addition amount of Mn; the metallographic structure is austenite, martensite and micro-nano precipitates, wherein the volume ratio of precipitates with a size of 2-50 μm is not less than 1.6%.
[0011] Preferably, the weight percentage of Cu is 1.3-4.3%.
[0012] Preferably, the weight percentage of Al is 5.6-11.5%.
[0013] A method for preparing layered heterogeneous lightweight high manganese steel containing nano-precipitates, comprising the following steps:
[0014] 1) After conventional smelting, pour or cut into required billet specifications;
[0015] 2) Heat the cast or cut steel billet at a temperature of 1120-1300°C and keep it at this temperature for 180-300 minutes;
[0016] 3) Hot rolling is performed, the hot rolling end temperature is controlled at 850-1000°C, and the total reduction rate is 30-60% and the rolling is performed to 5-
[0017] 10mm thickness;
[0018] 4) After coiling, air-cooling to room temperature, and then cold-rolling to product thickness at room temperature, and controlling the cumulative reduction rate to 50-80%;
[0020] 5) Performing aging treatment under argon protection, controlling the aging treatment temperature at 500-800° C., and keeping at this temperature for 3-10 hours, and controlling the oxygen content in the furnace to be ≤0.001wt% during the aging treatment;
[0021] 6) Allow to cool naturally to room temperature and set aside.
[0022] Preferably, the aging treatment temperature is controlled at 535-785° C.; the aging treatment holding time is negatively correlated to the holding temperature.
[0023] Preferably, the cumulative cold rolling reduction ratio is 55-75%.
[0024] The aging treatment method is: online or offline after coiling.
[0025] Mechanisms and functions of the main elements and processes in the present invention
[0026] C: C is the most economical and basic strengthening element in steel. It directly affects the strength, plasticity, toughness and welding performance of steel. It mainly strengthens steel through the precipitation of alloy carbides and interstitial solid solution. The addition of C can increase the stacking fault energy of austenite. In order to increase the volume fraction and stability of austenite and promote the formation of carbides, its content is controlled to ≤0.5%.
[0027] Si: Si is similar to Al. Adding Si can also reduce the mass density of austenitic steel. Every 1% Si added can reduce the density of steel by 0.8%. Adding Si accelerates the formation of κ-carbides. In order to promote the partition of C to carbides during the aging treatment process, its content is controlled to ≤0.5%.
[0028] Mn: Mn is an element that expands the austenite phase region and can increase the stacking fault energy of Fe-Mn-Al-C lightweight steel within a certain range. Mn has no obvious effect on the precipitation and growth of carbides, and increasing the Mn content will inhibit the formation of carbides to a certain extent. In order to expand the austenite phase region and increase the stacking fault energy of Fe-Mn-Al-C lightweight steel within a certain range, its content is controlled at 20.0-26.0%.
[0029] Al: Al is a ferrite-forming element and an important element for reducing the density of lightweight steel. In Fe-Mn-Al-C lightweight steel, the Al content can significantly affect the microstructure, mainly including the volume fraction of ferrite and whether carbides or other ordered phases are formed. At the same time, Al can significantly increase the stacking fault energy of Fe-Mn-Al-C lightweight steel, thereby affecting the deformation mechanism of the material. Therefore, the Al element is an important microstructure regulating element. In order to significantly promote the precipitation and growth of κ carbide in Fe-Mn-Al-C lightweight steel, its content is controlled at 5-12%.
[0030] Cr: Cr is a ferrite stabilizing element that can inhibit the formation of carbides and increase the ferrite content. The addition of Cr can improve the strength, corrosion resistance and formability of Fe-Mn-Al-C steel, thereby obtaining a lightweight steel with excellent corrosion resistance, high temperature oxidation resistance and creep resistance. In order to improve the strength, corrosion resistance and formability of Fe-Mn-Al-C steel, its content is controlled to ≤7%.
[0031] Cu: Adding Cu to Fe-Mn-Al-C lightweight steel can promote the precipitation of nano-sized Cu-rich phase and κ phase. As an austenite stabilizing element, Cu can increase the volume fraction of austenite, and its solid solution drag effect can also inhibit the occurrence of recrystallization. Cu-rich particles promote the formation of nano-κ phase, and the combined effect of the two is to improve the strength level of lightweight steel. In order to promote the precipitation of nano-sized Cu-rich phase and κ phase, its content is controlled at 0.5-5.0%.
[0032] Ni: Ni is easy to form B2 phase after adding Ni element to Fe-Mn-Al-C lightweight steel. After adding Ni, precipitation strengthening and solid solution strengthening work together to effectively hinder the movement of dislocations and promote the continuous hardening of the alloy. In order to easily form B2 phase, its content is controlled at 0.5-1.5%.
[0033] Nb: Nb is added to Fe-Mn-Al-C light steel to refine the austenite grain size. At the same time, these elements and C atoms can form carbides with high melting points and strong stability, which can effectively pin dislocations. In order to refine the austenite grain size and form carbides, its content is controlled at 0.01-0.5%.
[0034] P, S: Increased P and S content will promote the formation and growth of inclusions, resulting in decreased performance. Therefore, S≤0.006%, P≤0.015%.
[0035] The reason why the present invention controls the heating temperature of the steel billet to be 1120-1300°C and keeps the temperature at this temperature for 180-300 minutes is to reduce or eliminate the segregation of the chemical composition and microstructure of the steel ingot to make it uniform.
[0036] The reason why the hot rolling end temperature is controlled at 850-1000°C and the steel is rolled to a thickness of 5-10 mm at a total reduction rate of 30-60% is to improve the processing performance of metals and alloys, that is, to crush the coarse grains in the casting state, significantly heal the cracks, reduce or eliminate casting defects, transform the cast structure into a deformed structure, and improve the processing performance of the alloy.
[0037] The reason why the present invention cold-rolls to the product thickness at room temperature and controls the cumulative reduction rate to be 50-80% is to increase the internal stress and stacking fault energy of the material.
[0038] The reason why the present invention controls the aging treatment temperature at 500-800°C and keeps the temperature at this temperature for 3-10 hours and controls the oxygen content in the furnace to be ≤0.001wt% during the aging treatment is to make the material produce nano precipitates.
[0039] Compared with the prior art, the present invention can ensure that the yield strength is 900-1200MPa and the tensile strength is 1100-1320MPa, and the microstructure is austenite, martensite and nano-precipitates, the volume ratio of nano-precipitates with a size of 2-50nm is not less than 1.6%, and the elongation is ≥20%. In addition, the present invention is cold-rolled at room temperature, which is easier to industrialize. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 is the metallographic structure diagram of the lightweight dual-phase high manganese steel after being treated in the embodiment;
[0041] Figure 2 TEM of the precipitates in the lightweight dual-phase high manganese steel after treatment in Example. DETAILED DESCRIPTION
[0042] The present invention is described in detail below:
[0043] Table 1 is a list of chemical composition values of various embodiments and comparative examples of the present invention;
[0044] Table 2 is a list of main process parameters of various embodiments and comparative examples of the present invention;
[0045] Table 3 is a table of performance test results of various embodiments of the present invention and comparative examples.
[0046] Each embodiment of the present invention is produced according to the following steps:
[0047] 1) After conventional smelting, pour or cut into required billet specifications;
[0048] 2) Heat the cast or cut steel billet at a temperature of 1120-1300°C and keep it warm at this temperature.
[0049] 180~300min;
[0050] 3) hot rolling, controlling the hot rolling end temperature at 850-1000° C., and rolling to a thickness of 5-10 mm at a total reduction rate of 30-60%;
[0052] 4) After coiling, air-cooling to room temperature, and then cold-rolling to product thickness at room temperature, and controlling the cumulative reduction rate to 50-80%;
[0053] 5) Performing aging treatment under argon protection, controlling the aging treatment temperature at 500-800° C., and keeping at this temperature for 3-10 hours, and controlling the oxygen content in the furnace to be ≤0.001wt% during the aging treatment;
[0054] 6) Allow to cool naturally to room temperature and set aside.
[0055] Table 1 Chemical composition list of various embodiments and comparative examples of the present invention (wt%)
[0056]
[0057]
[0058] Table 2 List of main process parameters of various embodiments of the present invention and comparative examples
[0059]
[0060] Table 3 List of mechanical properties test results of various embodiments of the present invention and comparative examples
[0061]
[0062]
[0063] It can be seen from Table 3 that the present invention can ensure that the yield strength is 900-1200 MPa, the tensile strength is 1100-1320 MPa, the volume ratio of precipitates with a size of 2-50 nm is not less than 1.6%, and the elongation is ≥20%.
[0064] The above specific implementation modes are only the best examples and are not restrictive implementations of the technical solutions of the present invention.
Claims
1. A layered heterogeneous lightweight high manganese steel containing nano-precipitates, wherein the components and weight percentages thereof are: C≤0.5%, Si≤0.5%, Mn: 20.0-26.0%, Al: 5-12%, Cr≤7%, Cu: 0.5-5.0%, Ni: 0.5-1.5%, Nb: 0.01-0.5%, S≤0.006%, P≤0.015%, N≤0.001%, and the remainder is Fe and unavoidable impurities; and The amount of Al added is one quarter to one half of the amount of Mn added; the metallographic structure is austenite, martensite and micro-nano precipitates, wherein the volume ratio of precipitates with a size of 2 to 50 nm is not less than 1.6%.
2. The layered heterogeneous lightweight high manganese steel containing nano-precipitates according to claim 1, characterized in that: The weight percentage of Cu is 1.3-4.3%.
3. The layered heterogeneous lightweight high manganese steel containing nano-precipitates according to claim 1, characterized in that: The weight percentage content of Al is 5.6-11.5%.
4. The method for preparing a layered heterogeneous lightweight high manganese steel containing nano-precipitates according to claim 1, comprising the steps of: 1) After conventional smelting, pour or cut into required billet specifications; 2) Heat the cast or cut steel billet at a temperature of 1120-1300°C and keep it at this temperature for 180-300 minutes; 3) hot rolling, controlling the hot rolling end temperature at 850-1000° C., and rolling to a thickness of 5-10 mm at a total reduction rate of 30-60%; 4) After coiling, air-cooling to room temperature, and then cold-rolling to product thickness at room temperature, and controlling the cumulative reduction rate to 50-80%; 5) Performing aging treatment under argon protection, controlling the aging treatment temperature at 500-800° C., and keeping at this temperature for 3-10 hours, and controlling the oxygen content in the furnace to be ≤0.001wt% during the aging treatment; 6) Allow to cool naturally to room temperature and set aside.
5. The method for preparing a layered heterogeneous lightweight high manganese steel containing nano-precipitates according to claim 4, characterized in that: The aging treatment temperature is controlled at 535-785°C; the aging treatment holding time is negatively correlated with the holding temperature.
6. The method for preparing a layered heterogeneous lightweight high manganese steel containing nano-precipitates according to claim 4, characterized in that: The cumulative reduction rate of cold rolling is 55-75%.
7. The method for preparing a layered heterogeneous lightweight high manganese steel containing nano-precipitates according to claim 4, characterized in that: Aging treatment method: online or offline after coiling.
Citation Information
Patent Citations
Preparation method of a high-strength and high-plasticity TWIP steel
CN106191404B
1500 mpa-grade steel with high product of strength and elongation for vehicles and manufacturing method therefor
EP3492618B1